Adoption of digital intangible cultural heritage: a configurational study integrating UTAUT2 and immersion theory - Xinjie Ye; Yanwen Ruan; Sibei Xia; Liwen Gu (Humanities & Social Sciences Communications)
Abstract Intangible cultural heritage (ICH) is essential for promoting the sustainable development of the global economy and society. The rapid advancement of digital ICH technology and consumer hesitance underscore the necessity to examine customers’ willingness to adopt it. There is substantial research on the acceptability of digital ICH. However, various studies have yielded conflicting results regarding the impact of immersion technology on willingness to adopt it. Some studies claimed immersion technology provided users with a positive experience, while others argued it could lead to simulator sickness and distraction. This study utilised the unified theory of acceptance and use of technology (UTAUT2) and the immersion theory to develop a three-layer analytical framework. This framework examined consumer attitudes towards digital ICH from the perspectives of the target, context and process. This study evaluated the interconnections and collective impacts of factors to determine the willingness of customers to adopt digital ICH. A survey was designed, and 311 valid responses were received from individuals with prior exposure to digital ICH. The collected data was analysed using fuzzy-set qualitative comparative analysis (fsQCA) and necessary condition analysis (NCA). The study revealed important factors that strongly motivated customers to adopt digital ICH and the interaction between these factors. The research distinguished the characteristics of four distinct customer groups that are more willing to adopt digital ICH. This study provides theoretical insights and practical assistance for the safeguarding and advancement of ICH in the era of digital technology.